Evaluation of magnetic resonance imaging artifacts caused by fixed orthodontic CAD/CAM retainers: an in vitro study - Roser, Christoph; Hilgenfeld, Tim; Şen, Sinan; Badrow, Tobias; Zingler, Sebastian; Heiland, Sabine; Bendszus, Martin; Lux, Christopher J.; Jürchott, Alexander (Clinical oral investigations, 2021)
Magnetic resonance imaging (MRI) image quality can be severely impaired by artifacts caused by fixed orthodontic retainers. In clinical practice, there is a trend towards using computer-aided design/computer-aided manufacturing (CAD/CAM) retainers. This study aimed to quantify MRI artifacts produced by these novel CAD/CAM retainers.
Published online: 12 August 2020
Gesehen am 04.10.2021